Applying many of the methods to synchronization of chaos on the electronic circuit chaotic from type memductance - Yousif, Abu-Talib (Al-Qadisiyah Journal of Pure Science, 2020)
Abstract : the attractor chaotic from the type Chua’ attractors, was obtained at study one types of electronic circuit chaotic affiliate for family Chua’ circuit, where, the nonlinear part from type memductance, after we succeeded in found the attractor chaotic for circuit, we study many from the methods of synchronization chaos. It was the first method is Pecora and Carroll (PC), but it failed to reach for case complete synchronization, because the ratio of error not equal zero. The same as of result can reach for it, when we applying the method of adaptive-observer, at choose the value of feedback gain c=10. In addition to that, we discussed another method call adaptive feedback synchronization, which Succeed complete synchronization, and the ratio error equal to zero, but exist some noise, which can get rid of it by using the low frequency filter. Also, we suggested new method from the type feedback, which also achieved the complete synchronization, and the noise is disappear clearly, in the method adaptive the complete synchronization achieved after time t=0.05s.